Production of Triacetin by Microwave Assisted Esterification of Glycerol Using Activated Natural Zeolite - Marwan Marwan; Eti Indarti; Darmadi Darmadi; Wahyu Rinaldi; Dzikri Hamzah; Taufik Rinaldi (Bulletin of Chemical Reaction Engineering & Catalysis, 2019)
Triacetin, an alternative biodiesel additive, was prepared by esterification of glycerol with acetic acid in the presence of chemically activated natural zeolite. The esterification was carried out in a small reaction flask under microwave irradiation. The catalyst was characterized for its morphology by SEM and its chemical composition by X-ray Diffraction (XRD). The Scanning Electron Microscopy (SEM) micrograph indicates improved surface area of the zeolite, while the XRD analysis shows an increase in Si/Al ratio from natural zeolite to 6.042 and its crystallinity value of 12.23%. The Fourier Transform Infra Red (FTIR) analysis obtained showed that microwave-heated samples have an esters group spectrum of triacetin at 1702 cm-1. The conversion value of glycerol was more than 95% at molar ratio of the reactants 1:9 and catalyst loading of 3%. The selectivities for monoacetin, diacetin and triacetin were 80.1%, 15.4%, and 4.5% at 60 minutes, and 43.0%, 48.6%, and 8.3% at 90 minutes. It shows that the conversion took place in consecutive steps and the use of microwave allows the reaction proceeding at milder condition.